The nature of Supreme Court power - Hall, Matthew Eric Kane (Cambridge University Press, 2011)
"This book offers a comprehensive theory of Supreme Court power, identifying conditions under which the Court is successful at altering the behavior of state and private actors. Matthew E. K. Hall depicts the Court as a powerful institution, capable of exerting significant influence over social change"-- Provided by publisher.